2018
DOI: 10.1096/fj.201801015r
|View full text |Cite
|
Sign up to set email alerts
|

Normalizing adiponectin levels in obese pregnant mice prevents adverse metabolic outcomes in offspring

Abstract: Infants of obese mothers have an increased risk of developing obesity, insulin resistance, and type 2 diabetes. The underlying mechanisms remain elusive, and no effective interventions to limit the transmission of metabolic disease from the obese mother to her infant are currently available. Obese pregnant women have decreased circulating levels of adiponectin, which is associated with increased placental nutrient transport and fetal overgrowth. We have reported that normalization of adiponectin levels during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 55 publications
(81 reference statements)
4
29
0
Order By: Relevance
“…Maternal adiponectin infusion in these obese mice led to a normalisation of maternal insulin sensitivity, nutrient transport, placental insulin/mTORC1 and PPARα signalling and fetal growth independent of the effects on maternal fat mass (Aye et al 2015). Further work by Paulsen et al has also shown that normalisation of adiponectin levels of maternal obesity in the mouse prevented the development of adverse metabolic outcomes in male offspring (Paulsen et al 2018) and thus suggests that low circulating maternal adiponectin may represent a critical mechanistic link between a maternal obesogenic environment and the development of metabolic disease in offspring.…”
Section: Intervention Strategiesmentioning
confidence: 92%
“…Maternal adiponectin infusion in these obese mice led to a normalisation of maternal insulin sensitivity, nutrient transport, placental insulin/mTORC1 and PPARα signalling and fetal growth independent of the effects on maternal fat mass (Aye et al 2015). Further work by Paulsen et al has also shown that normalisation of adiponectin levels of maternal obesity in the mouse prevented the development of adverse metabolic outcomes in male offspring (Paulsen et al 2018) and thus suggests that low circulating maternal adiponectin may represent a critical mechanistic link between a maternal obesogenic environment and the development of metabolic disease in offspring.…”
Section: Intervention Strategiesmentioning
confidence: 92%
“…In the grouped analyses, male offspring of dams on control diet were used as the control group. Experimental numbers (n/group) were determined using previous studies by our group [ 43 ], as well as expertise from the mouse phenotyping core at The University of Minnesota. Data are presented as mean ± SEM.…”
Section: Methodsmentioning
confidence: 99%
“…In this mouse model of HFHC-induced maternal obesity, we previously observed that male, but not female, HFHC offspring, gain excess weight at 8–9 weeks postnatal age on a standard chow diet [ 43 ]. At 14 weeks of age, maternal HFHC-diet-exposed male offspring, but not female offspring, show evidence of adiposity, glucose intolerance, insulin resistance, fatty liver, and cardiac dysfunction [ 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations